2018
DOI: 10.1016/j.marpolbul.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

High genetic variability of Alexandrium catenella directly detected in environmental samples from the Southern Austral Ecosystem of Chile

Abstract: Chilean waters are often affected by Alexandrium catenella, one of the leading organisms behind Harmful Algae Blooms (HABs). Genetic variability for this species are commonly carried out from cultured samples, approach that may not accurately quantify genetic variability of this organism in the water column. In this study, genetic variability of A. catenella was determined by sequencing the rDNA region, in water samples from the Canal Puyuhuapi (South Austral Ecosystem of Chile). A. catenella was detected in 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
5
4
0
Order By: Relevance
“…The authors found 33 haplotypes, three of these highly frequent, increasing the genetic diversity from 2.8 to 3.1%, for this species in the study area. All sequences agreed with the morphological identification for A. catenella, with sub-clades that correspond to haplotypes from distinct geographic regions (Cruzat et al, 2018).…”
Section: Molecular Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…The authors found 33 haplotypes, three of these highly frequent, increasing the genetic diversity from 2.8 to 3.1%, for this species in the study area. All sequences agreed with the morphological identification for A. catenella, with sub-clades that correspond to haplotypes from distinct geographic regions (Cruzat et al, 2018).…”
Section: Molecular Studiessupporting
confidence: 70%
“…This was the first report of A. minutum and A. ostenfeldii on this area of Argentinean Sea (Fabro et al, 2017). Cruzat et al (2018) determined genetic variability of A. catenella analyzing ITS1-5.8S-ITS2 sequences of ribosomal DNA of environmental samples from the Southern Austral ecosystem. The authors found 33 haplotypes, three of these highly frequent, increasing the genetic diversity from 2.8 to 3.1%, for this species in the study area.…”
Section: Molecular Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Phenotypic plasticity and genetic variability has been reported for A. catenella strains (Group I) from Chile, Mediterranean Sea, and Japan (Penna et al, 2005;Cruzat et al, 2018). Alpermann et al (2009) reported phenotypic and genetic variability in A. tamarense isolates (Group III) from the North Sea coast of Scotland that were interpreted, respectively, as having strong potential for adaptability of the population and evidence for a lack of strong selective pressure on respective phenotypic traits at the time the population was sampled.…”
Section: Discussionmentioning
confidence: 99%